2019
DOI: 10.9734/jpri/2019/v31i430305
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Individual Medication Adherence among Chronic Kidney Disease Patients: A Multi-centered Study

Abstract: Aims: This study aims to identify differences in outcomes of assessing overall versus individual adherence and factors associated with adherence to medication therapy in chronic kidney disease patients. Study Design:  This is a cross-sectional study. Place and Duration of Study: Nephrology Clinic, Universiti Kebangsaan Malaysia Medical Centre and Ministry of Health Hospitals between June 2018 and June 2019. Methodology: We included 491 patients (243 men, 248 women); average age of 54.5 (±14.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Poor adherence increases the risk of adverse events or medication efficacy loss, which then require frequent adjustments to, or intensification of medication regimen [ 8 , 11 ]. Poor adherence is multifactorial [ 2 , 4 , 31 , 32 ], with high medication burden and complex administration regimen often associated with poor adherence [ 32 ]. In addition, poor adherence is associated with poorer blood pressure control [ 4 ] and increased risk of CKD progression [ 4 , 31 ], which ultimately lead to changes in medications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Poor adherence increases the risk of adverse events or medication efficacy loss, which then require frequent adjustments to, or intensification of medication regimen [ 8 , 11 ]. Poor adherence is multifactorial [ 2 , 4 , 31 , 32 ], with high medication burden and complex administration regimen often associated with poor adherence [ 32 ]. In addition, poor adherence is associated with poorer blood pressure control [ 4 ] and increased risk of CKD progression [ 4 , 31 ], which ultimately lead to changes in medications.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this work demonstrates the need for pharmacists to strengthen CKD patient care, among those with antihypertensive drug adjustments, via monitoring their medication adherence, TCM use, albuminuria status, as well as education on correct medication knowledge, belief and management skills [ 31 , 33 ]. Knowledge of CKD and treatment delays CKD progression and minimises CKD complications [ 2 ]. The potential benefits of pharmacist involvement are beyond the improvement of medication adherence, ranging from reduced hospitalisation rates to increased savings to healthcare systems [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, Kim and Evangelista[ 41 ] found that treatment control had a significant correlation with non-adherence, i.e., patients with a higher level of perception of uncontrollability of their illness displayed a higher nonadherence. In addition, three studies investigated patients' medication knowledge and these studies found that patients were more likely to be nonadherent when they have less medical knowledge about the medication, they have been prescribed[ 37 38 41 ].…”
Section: R Esultsmentioning
confidence: 99%